Halal Blood Supply Chain Analysis Using the House of Risk Method - Faiza Mufid, Nisrina; Mansur, Agus; Noor Said, Rajiv; Binti Paozi , Norhidaya (Spektrum Industri, 2026)
The absence of halal assurance mechanisms in blood donation systems presents an urgent challenge in ensuring both medical safety and halal compliance within the blood supply chain (BSC), particularly in Indonesia where over 87% of the population is Muslim. The lack of official halal certification for blood donation poses risks to religious integrity and public trust. Issues such as uncertified materials, inadequate handling supervision, and potential mixing of non-halal blood emphasize the need for a systematic approach integrating medical safety and halal assurance in BSC management. This study contributes theoretically by introducing the concept of a halal blood supply chain and establishing a structured framework for managing halal-related risks in blood donation through the integration of the House of Risk (HOR) model and the Supply Chain Operations Reference (SCOR) framework. Practically, this study offers a risk-based decision support tool for blood service institutions by identifying key halal-related risks and actionable mitigation strategies. Empirically, this research employed the HOR–SCOR framework to identify, assess, and prioritize potential sources of non-halalness in the blood donation operations of PMI Sleman Regency. Data were collected through interviews, observations, and expert validation. The analysis covered 28 risk events and 35 risk agents, quantified using the Aggregate Risk Potential (ARP) and Effectiveness-to-Difficulty (ETD) ratios to determine the most critical risks and appropriate mitigation actions. The results identified four major risk sources: the absence of written halal blood criteria, improper storage temperature, misinterpretation of test results, and machine errors in the crossmatching process. The findings indicate that applying the HOR framework effectively reduces halal-related risks while enhancing operational reliability, transparency, and Shariah compliance within blood donation systems. Furthermore, this study provides a foundation for developing a national halal BSC model and certification system in collaboration with relevant authorities such as BPJPH and MUI.